TINGKAT PARTISIPASI KELOMPOK TANI TERHADAP PROGRAM HUTAN KEMASYARAKATAN (HKm) DI DESA TEBAT PULAU KECAMATAN BERMANI ULU KABUPATEN REJANG LEBONG - Rahabillah Firdha; Herlina -; Herri Fariadi (UNIVED Press, Universitas Dehasen Bengkulu, 2014)
Forestry development in Indonesia is regulated by a system of laws and regulations in orderto mememenuhi pattern of sustainable forestry development with reference to Law 41 then was issued a government policy which began to provide space and public access around the forest to forest. Government policy in the form of the issuance of the Minister of Forestry Regulation. P.37/Menhut-II/2007 on community forestry, which is subsequently followed by the changes and improvements (Permenhut No.P.18/Menhut-II/2009, No. Permenhut. P.13/Menhut-II/2010, until Permenhut No.P52/Menhut-II/2011). The method used in the sampling done by purposive sampling. The data used is primary data from respondents to the structured interview, questionnaire (Questionnaire), and observation. Secondary data from various agencies such as, Government, stakeholders and supporting literature. Then analyzed using descriptive analysis with a qualitative and quantitative approach, in which the results of this study are described in detail in providing a clear and comprehensive picture of people's participation in community forestry. The results showed the level of participation in community forest farmer groups dam village in the island of socialization (98.57%), monitoring (82.86%) and evaluation (86.43%) is high, whereas at the level of group participation in work planning and implementation of community forestry programs are being (58.81%). While the overall participation recapitulation is 81.67% higher.Keywords: Participation, Farmer Groups, Community Forestry Program